The role of private quality and safety management systems in reducing consumer risks by plant protection residuals in the fields of the vegetable and fruit sector - Lehota, József; Szabó, Zoltán; Lehota, Zsuzsanna (The Hungarian Journal of Marketing and Management, 2019)
The risks related to the traditional industry agricultural technologies including the plant protection residuals became more and more obvious during the last decades. The perceived risks related to the plant protection residuals in Hungary increased in comparison to international standards to an outstanding level. The means reducing risks got higher importance and became a crucial factor in increasing consumption. One of the options to reduce risks is the spread of low input technologies and the other possibility is to improve the quality management and food safety systems of the trade (wholesale, retail).